2020
DOI: 10.3389/fsufs.2020.00125
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic Nematodes in Sustainable Food Production

Abstract: The emphasis of this review is on the use and potential of entomopathogenic nematodes (EPNs) as biological control agents in sustainable food production across a wide range of agricultural and other commodities. To aid with the understanding of the potential of EPNs in sustainable food production, this review also provides overviews on EPN biology and ecology, mass production and application technology, and interactions with other management tools. First discovered in the 1920s, their commercialization as biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 111 publications
0
67
0
1
Order By: Relevance
“…Entomopathogenic nematodes proved high efficiency in killing several species of insect pests; some are specific to a particular insect host or even a specific developmental stage while others have a wide range of hosts (Odendaal et al, 2016;Williams et al, 2015). Hence, a few EPNs can be used as commercial products against some insects in the field application (Georgis et al, 2006;Koppenhöfer et al, 2020;Askary and Abd-Elgawad, 2021), and these is depending on the suitability of this host to the nematode species (Dillman et al, 2012). In this study, the four selected EPN species were highly effective in killing the two insect hosts, Galleria mellonella and Spodoptera littoralis.…”
Section: Discussionmentioning
confidence: 82%
“…Entomopathogenic nematodes proved high efficiency in killing several species of insect pests; some are specific to a particular insect host or even a specific developmental stage while others have a wide range of hosts (Odendaal et al, 2016;Williams et al, 2015). Hence, a few EPNs can be used as commercial products against some insects in the field application (Georgis et al, 2006;Koppenhöfer et al, 2020;Askary and Abd-Elgawad, 2021), and these is depending on the suitability of this host to the nematode species (Dillman et al, 2012). In this study, the four selected EPN species were highly effective in killing the two insect hosts, Galleria mellonella and Spodoptera littoralis.…”
Section: Discussionmentioning
confidence: 82%
“…With the multiplicity and variety of experiments they are involved in, insecticidal nematodes advance and occupy a suitable position among other biopesticides for T. semipenetrans control as well (e.g., Abd-Elgawad et al, 2013;Abd-Elgawad, 2017a, b). New directions are developing to leverage EPN efficacy with costs-effective techniques comprise optimizing sampling and extraction methods (Abd-Elgawad, 2020c; Abd-Elgawad, 2021b), detecting and/or developing enhanced strains, lowering costs of mass production, formulation and application technology, adequate combination with other control tactics (Abd-Elgawad and Askary, 2021), and environmental manipulation (Koppenhöfer et al, 2020;Dritsoulas et al, 2021). For instance, application is eased by a variety of formulations that offer stability and favorable use, e.g.…”
Section: Nematicidal Applicationmentioning
confidence: 99%
“…However, lack of sufficient information regarding the diversity of Xenorhabdus within the species limits the application of these bacteria. Moreover, although many valid species of Steinernema and Heterorhabditis have been described (e.g., Shapiro-Ilan et al 2020), only 13 of these identified species have been commercialized till now (Koppenhöfer et al 2020a). This fact provides a scope to exploit the other species.…”
Section: Opportunitiesmentioning
confidence: 99%